A curious case of electric wire in urethra - Thangarasu, Mathisekaran; Prakash, Sanjay J.; Jain, Nitesh (International Surgery Journal, 2020)
We present a case of discharging urethral fistula in a sexually active young male, who was found to have an impacted electrical wire in the urethra. Polyembolokoilamania is a condition, where one inserts foreign bodies via natural orifices, either for autoerotism, in inebriated states or due to psychological conditions. A wire was inserted into the patient’s urethra and it remained impacted for a year, leading to pain, dysuria and discharging urethral fistula. The wire was removed and the fistulous tract was excised. Patients, if diagnosed with autoerotism needs follow up with psychiatrist to address the underlying condition.